The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4cc02605e
|View full text |Cite
|
Sign up to set email alerts
|

A general protein purification and immobilization method on controlled porosity glass: biocatalytic applications

Abstract: PostprintThis is the accepted version of a paper published in Chemical Communications. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…(56% e.e., entry 7), the best results were obtained with EziG3, a carrier with a semi‐hydrophilic surface (Table , entry 10 Figure S8). The carrier EziG, based on glass beads, was used to overcome the compressibility of the alginate beads which may cause problems when used in flow. The carrier links the enzyme via Fe 2+ ions at the surface which possess according to the supplier enhanced binding strength toward the His‐tag.…”
Section: Resultsmentioning
confidence: 99%
“…(56% e.e., entry 7), the best results were obtained with EziG3, a carrier with a semi‐hydrophilic surface (Table , entry 10 Figure S8). The carrier EziG, based on glass beads, was used to overcome the compressibility of the alginate beads which may cause problems when used in flow. The carrier links the enzyme via Fe 2+ ions at the surface which possess according to the supplier enhanced binding strength toward the His‐tag.…”
Section: Resultsmentioning
confidence: 99%
“…5MP functionalized solid supports were prepared by treating commercially available long chain aminoalkyl controlled porosity glass (LCAA-CPG) 37 with freshly prepared 1′ at pH 7.5 for 4 h. Quantitation of free amines on the support before and after the reaction using 4-chloro-7-nitrobenzofurazan 38 revealed that 5MP functionalization proceeded essentially to completion. Mixing ilvN with 5MP-CPG resulted in quantitative protein immobilization in less than 10 min (Figure S49).…”
Section: Resultsmentioning
confidence: 99%
“…Immobilization on EziG and co‐lyophilization with surfactants : Immobilization of SC on hydrophobic EziG 2 material was made by using sterile, filtered (0.45 and 0.2 μm) cell culture supernatant to obtain simultaneous protein purification and immobilization . The EziG 2 material was added in fourfold excess relative to the amount of protein in solution.…”
Section: Methodsmentioning
confidence: 99%
“…Immobilization of SC on hydrophobic EziG 2m aterial was made by using sterile, filtered (0.45 and 0.2 mm) cell culture supernatant to obtain simultaneous protein purification and immobilization. [64] The EziG 2m aterial was added in fourfold excess relative to the amount of protein in solution. For SC wild type, approximately 300 mg EziG 2p er liter cell culture supernatant was applied.…”
Section: Immobilization On Ezig and Co-lyophilization With Surfactantsmentioning
confidence: 99%